The student’s drawing of teacher’s pictorial Value as a predictor of the student–teacher relationship and school adjustment - Di Norcia, Anna; Bombi, Anna Silvia; Pinto, Giuliana; Cannoni, Eleonora (Frontiers in Psychology, 2022)
This study employs the scale of Value from Pictorial Assessment of Interpersonal Relationships (PAIR) to investigate the links between the importance attributed by primary students to their teachers and two independent measures of scholastic wellbeing, provided by teachers and parents. During middle childhood, the teacher is one of the most significant adults with whom children interact daily; a student–teacher relationship warm and free from excessive dependency and conflict is very important for children wellbeing; however, children’s recognition of teacher importance as an authority figure has been seldom studied. Children aged 7–11 years were individually asked to draw themselves and one of their teachers in two situations (relational Wellbeing and relational Distress); the scale of Value from PAIR was used as a proxy of the importance attributed to teachers in each situation. Teachers completed the Student–Teacher Relationship Scale for Closeness, Conflict, and Dependency of each child; parents answered two items about their children’s School Adjustment. All the study variables were firstly analyzed to check gender and age differences. Boys valorized more than girls the teacher’s figure; however, teachers perceived more Closeness and less Conflict with girls. Dependency and Conflict decreased with age, as well as (albeit slightly) School Adjustment. To assess the links between pictorial valorization of the teacher in Wellbeing and Distress and teachers’ and parents’ evaluations, four separate hierarchical regressions were performed, namely, Closeness, Dependency, Conflict, and School Adjustment, controlling children’s sex and age. The teacher’s pictorial Value in Wellbeing appeared to be related to Closeness and School Adjustment, while a negative relationship emerged between Value and Dependency in Distress. In sum, the recognition of the teacher’s role as an authority figure does not hinder a warm student–teacher relationship and impacts positively on school adjustment. In situations of Distress, dependent pupils showed a diminished appreciation of the teacher’s importance, possibly as a result of a defensive stance.